A Morphological Analysis of Derivational Morphemes in BBC Business News Articles and Its Implications for EFL Vocabulary Learning - Badri, Badri; Miftah, Miftah Komala Putri; Mardiyah, Mardiyah; Suhendra, Adi; Hasanah, Rosyidah; Hekmatiar, Yusuf (English Education, Linguistics, and Literature Journal, 2026)
Derivational morphology plays a crucial role in expanding English vocabulary and contributes significantly to lexical development in authentic written discourse. However, studies examining derivational morphemes in business news articles and their implications for English as a Foreign Language (EFL) vocabulary learning remain limited. This study aims to identify the types of derivational morphemes that occur in BBC Business News articles, analyse their morphological functions, and explore their implications for EFL vocabulary learning. Employing a descriptive qualitative approach, the study analyzed five BBC Business News articles selected through purposive sampling. The data consisted of lexical items containing derivational morphemes, which were identified, classified, and analyzed based on Carstairs-McCarthy's (2002) theory of English morphology and Bauer's (2003) concept of morphological productivity. The findings reveal that suffixation is considerably more productive than prefixation, with noun-forming suffixes such as -tion, -ation, -ment, and -ity, as well as adjective-forming suffixes including -al, -ic, and -ial, occurring most frequently. Furthermore, class-changing derivation predominates over class-maintaining derivation, indicating that business journalism relies heavily on lexical expansion through nominalization and adjective formation to communicate complex economic concepts effectively. These findings highlight the pedagogical value of authentic BBC Business News articles in fostering EFL learners' morphological awareness, vocabulary development, and reading comprehension. The study contributes to English Applied Linguistics by providing empirical evidence of the productive use of derivational morphology in contemporary business news discourse and supporting the integration of authentic news texts into morphology-based vocabulary instruction.